Snare Guiding Technique in Bifurcated Endovascular Repair of Abdominal Aortic Aneurysm with Severely Tortuous Iliac Artery Access: A Case Report - Hariyono, Dedy Chandra; Hayuningrat, Prima Kharisma; Utomo, Arif Prasetyo; Yarsa, Kristanto Yuli; Ismail, Darmawan (Malaysian Journal of Medicine and Health Sciences, 2022)
Endovascular aneurysm repair (EVAR) has gained acceptance as a viable alternative to open surgical treatment for abdominal aortic aneurysm (AAA). We report the use of snare guiding wire in bifurcated EVAR case with severely tortuous femoral access. A 63-year-old man referred to the hospital from another facility with complaints of pulsating mass in right iliac and umbilical region for the last 2 years. He was then admitted to the cardiac catheterization lab for EVAR under general anaesthetic. Endovascular aneurysm repair (EVAR), also known as an endoprosthesis, is a stent-graft device-guided therapy for a AAA. This procedure is a safer choice for individuals who are elderly or have pulmonary, cardiac, or renal problems. Tortuous iliac arteries might obstruct device delivery during EVAR. The Snare Guiding Wire approach might be an alternate method for EVAR to treat AAA if conventional cannulation is difficult or impossible in individuals with highly tortuous iliac access.